Standardised flavonoid extract from Diospyros kaki L.f leaves alleviates high blood pressure and ventricular hypertrophy on cortisone acetate-induced hypertensive rats - Thi Thanh Loan Nguyen; Thi Van Anh Pham; Thi Xoan Le (Vietnam Journal of Science, Technology and Engineering, 2023)
The current study was designed to investigate the anti-hypertensive effects of a standardised flavonoid extract from Diospyros kaki L.f leaves (DK extract) on cortisone acetate-induced hypertensive rats. Hypertension was induced in Wistar rats by subcutaneously injecting 2.5 mg cortisone acetate daily and by maintaining the rats on a 1% sodium chloride diet for a period of 28 days. The hypertensive rats were treated daily with DK extract (50 and 100 mg/kg of body weight; p.o.) or captopril (20 mg/kg of body weight; p.o.), a reference drug, for 14 consecutive days. The blood pressure and heart rate of awake rats were measured using a non-invasive tail-cuff method. The heart weight and left ventricular wall thickness of rats were measured. In vitro angiotensin-converting enzyme (ACE) inhibition activity of the DK extract and captopril were analysed. DK extract significantly and dose-dependently reduced systolic and diastolic blood pressure in the hypertensive rats. There were no significant changes observed in heart rate. The cortisone acetate-induced hypertensive rats had increased heart weight and left ventricular wall thickness. These actions were attenuated by the treatment of DK extract (100 mg/kg) and captopril. Moreover, DK extract inhibited ACE activity in vitro with an IC50 of 4.71±0.53 µg/ml. Our findings demonstrate that DK extract exerted anti-hypertensive effects and alleviated ventricular hypertrophy in the cortisone acetate-induced hypertensive rats and these actions occurred at least in part via ACE activity inhibition.